TINJAUAN YURIDIS PENGAJUAN PRAPERADILAN LEBIH DARI SATU KALI DALAM HUKUM ACARA PIDANA DI INDONESIA - Kurnia, Radhi; Indra, Mexsasai; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Filing pretrial more than one time in criminal procedural law into research background, the Criminal Procedure Code as the basis for litigation pretrial does not explain the filing of pre-trial more than once, the Criminal Procedure Code only mmemunginkan someone to file pretrial without restrictions or ideal concept of filing pretrial more than one time. Pretrial filing more than one time to make the law enforcement process protracted and legal certainty are not implemented. This type of research can be classified in this type of normative legal research, which examines the general principles of law and perbandinganhukumterhadap a legal event. To draw conclusions from the data collected, the authors used data analysis techniques deductive, that is by drawing conclusions that are special. From the research problem there are two things that can be inferred. First, pretrial filing more than one still accepted by the judge even though no rules were discussed. Second, the concept of pretrial ideal is the appointment of special judges, registration and inspection of pretrial matters should be attended by the suspect in question. Suggestions Writer, first, it is recommended that immediately made arrangements firmly on pretrial which can only be done once the by revisions to the Criminal Procedure Code, or at least the Supreme Court issued PERMA (Rules of the Supreme Court) on a pre-trial can only be done one kali.Kedua, is expected in the future pretrial case investigation is conducted by a special judge, the parties filed a lawsuit petition shall be attended by the suspect in question, the case investigation pretrial attended by the suspect to the interests of the suspect can be proved at trial. Keywords : Pretrial - Criminal Proceedings